Saphic Features in QS. al-Fātiḥah (Study of Tafsīr al-Khaṭīb al-Makkī Works of Abdul Hamid al-Minangkabawi) - Alfarabi, Ahmad Syah; Zakiah, Nita; Helty, Ainun (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Tafsīr al-Khaṭīb al-Makkī by Abdul Hamid al-Minangkabawi is commonly recognized for its dominant features of tafsīr al-fiqhī (jurisprudential exegesis) and tafsīr al-ādabī al-ijtimāʿī (literary-social exegesis). Consequently, the Sufi dimensions of Abdul Hamid’s thought have received relatively limited scholarly attention, despite biographical accounts that highlight his deep engagement with Sufism. This study aims to examine the Sufi exegetical style evident in his interpretation of Sūrat al-Fātiḥah. The research employs a qualitative library-based method with a descriptive-analytical approach. The findings reveal Sufi-oriented interpretations in Tafsīr al-Khaṭīb al-Makkī, specifically in verse 2 (rabb al-ʿālamīn) and verse 5 (iyyāka naʿbudu wa iyyāka nastaʿīn). These verses exemplify features of tafsīr al-ṣūfī al-ishārī, wherein the interpretive meanings transcend the literal (ẓāhir) and are informed by esoteric insights received through spiritual unveiling (kashf) experienced by the Sufi. Nonetheless, these meanings do not necessarily contradict the outward interpretations, allowing for a reconcilable synthesis. This style may also be categorized as taṣawwuf ʿamalī (practical Sufism), whereby Qur’anic verses are understood through subtle inner signs manifest in a Sufi’s personal spiritual experience and devotional practice.